Legal Protection For Notary Employees As Instrumentary Witnesses Regarding The Principle Of Deed Confidentiality By Investigators - Lalu Ghazy Sultansah Abdurrahman; Lalu Hadi Adha; Kurniawan (Faculty of Law, University of Mataram, 2026)
The examination of notary employees as instrumentary witnesses in criminal investigations often triggers conflicts between investigative authority and the obligation to maintain professional secrecy. Normatively, instrumentary witnesses only verify the formal execution of authentic deeds and are not privy to their legal substance. In practice, however, interrogations frequently exceed these formal limits. This study aims to analyze the discrepancy between norms and practices, while formulating a concrete legal protection model for these witnesses. Employing normative legal research with statutory and conceptual approaches, the study reveals that the current vulnerability arises from a distinct regulatory vacuum: neither the Indonesian Notary Act (UUJN) nor the Criminal Procedure Code (KUHAP) grants explicit procedural safeguards or a derivative right of refusal (hak ingkar) to notarial staff. To bridge this gap, this article establishes its academic novelty by proposing a “Derivative Protection Model.” This model advocates for extending the Notary Honor Council’s (MKN) protective mandate to instrumentary witnesses and institutionalizing a derivative hak ingkar within procedural law, ensuring a balanced synergy between criminal law enforcement and the sanctity of notarial confidentiality.